PENGARUH PENGGUNAAN PLATFORM DIGITAL MONEY DAN PLATFORM E-COMMERCE TERHADAP PERILAKU KONSUMTIF MAHASISWA - Wati Arifin, Mila Rahma; Cahya, Septyan Budy (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
The COVID-19 pandemic has driven an increase in the adoption of digital platforms, especially digital money platforms and e-commerce among the public, including students who are one of the groups with high levels of digital consumption. This study aims to analyze the effect of using digital money and e-commerce platforms on consumptive behavior among students of the Faculty of Economics and Business (FEB), Surabaya State University. The research method used is a quantitative approach with an experimental design. The research subjects were 378 students of FEB Surabaya State University class of 2020-2023 who actively use digital money and e-commerce platforms. Data collection was carried out through distributing questionnaires using a likert scale. Data analysis was performed using multiple linear regression techniques. The results showed that the use of digital money platforms and e-commerce platforms had an effect on student consumptive behavior, both partially and simultaneously. So it can be concluded that the higher the use of digital money and e-commerce platforms, the greater the tendency of consumptive behavior shown by students.